ChemInform Abstract: Exploitation of the Ugi—Joullie Reaction in the Synthesis of Libraries of Drug‐Like Bicyclic Hydantoins. Issue 1 (17th December 2015) - Firth, James D.; Zhang, Rong; Morgentin, Remy; Guilleux, Rachel; Kalliokoski, Tuomo; Warriner, Stuart; Foster, Richard; Marsden, Stephen P.; Nelson, Adam
Abstract: Bicyclic hydantoins are efficiently obtained utilizing a three‐component Ugi—Joullie reaction/cyclization sequence as key complexicity‐generation process using trifluoroacetic acid as synthetic equivalent for chloroformic acid.